Associations between Maternal Nutritional Status, Carbohydrate, Fat, and Protein Intakes, and Low Birth Weight in Jember, East Java - Winasandis, Brillia Firsti; Tamtomo, Didik; Anantanyu, Sapja (Journal of Maternal and Child Health, 2020)
Background: Pregnancy can cause several bodily changes, both anatomically, physiologically, and biochemically. Mothers' metabolism and food intake will change during pregnancy. Food intake of pregnant women will increase every trimester, so it must be considered because it is not only for herself, but for the fetus she is carrying. Excessive carbohydrate intake has an adverse effect on babies born, lack of excessive intake is also not good. This study aims to analyze the association between nutritional status, carbohydrate, fat, and protein intakes of pregnant women with birth weight (BBL). Subjects and Methods: This was a cohort study conducted at community health center in Jember, East Java, from April to June 2019. The sample was randomly selected as many as 120 study subjects. The dependent variable was birth weight (LBW). The independent variables were carbo